Prinsip-Prinsip Demokrasi dalam Prespektif Hadis - Ibya Zaynah; Muhammad Alif (STIKes Ibnu Sina Ajibarang, 2025)
The principles of democracy in the Hadith perspective reflect Islamic beliefs that emphasize the values of equality, deliberation, and justice. Although the word “democracy” is not found in the hadith texts, the teachings on the basic principles of democracy contain and underlie people's participation, freedom of speech, and respect for the rights of each individual that can be found in the teachings of the prophet Muhammad SAW. Hadiths related to deliberation (shura), social justice, and leader selection indicate that decision-making in society should be based on inclusiveness, transparency, and responsibility. For example, hadith-reports that suggest deliberation in dealing with important issues indicate respect for individual voices and opinions in a collective decision. In addition, the concept of justice in the hadith emphasizes the importance of equal treatment of all members of society without discrimination. The purpose of this article is to provide knowledge about democracy in the Hadith perspective in the perspective of hadith. Thus, the hadith perspective provides a moral and ethical foundation for the implementation of democratic principles that are oriented towards the welfare of the people and the fair management of public interests.